Harry Potter as High Fantasy (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Born on July 31, 1965, in Yate, near Bristol, England, British author J.K. Rowling is best known for writing the bestselling Harry Potter series, which follows the adventures of a young wizard as he trains to become a powerful wizard. The Harry Potter books have broken sales records and become literary classics. From being in need of government aid to being worth tens of millions of dollars—all in only five short years—that's Rowling. If you're looking for a famous British writer, Joanne is your girl. My academic pursuits are wholly devoted to the study of fantastic and science fiction literature. As a critic of children's literature, I'd want to take a look at how the pictures, symbols, and strategies used in the Harry Potter series shape our imaginary world. All through it, the author stresses how far from reality imagination exists.